Sociodemographic, psychiatric and somatic risk factors for suicide: a Swedish national cohort study. Issue 2 (23rd April 2013) - Crump, C.; Sundquist, K.; Sundquist, J.; Winkleby, M. A.
Abstract : Background: More effective prevention of suicide requires a comprehensive understanding of sociodemographic, psychiatric and somatic risk factors. Previous studies have been limited by incomplete ascertainment of these factors. We conducted the first study of this issue using sociodemographic and out-patient and in-patient health data for a national population. Method: We used data from a national cohort study of 7140589 Swedish adults followed for 8 years for suicide mortality (2001–2008). Sociodemographic factors were identified from national census data, and psychiatric and somatic disorders were identified from all out-patient and in-patient diagnoses nationwide. Results: There were 8721 (0.12%) deaths from suicide during 2001–2008. All psychiatric disorders were strong risk factors for suicide among both women and men. Depression was the strongest risk factor, with a greater than 15-fold risk among women or men and even higher risks (up to 32-fold) within the first 3 months of diagnosis. Chronic obstructive pulmonary disease (COPD), cancer, spine disorders, asthma and stroke were significant risk factors among both women and men (1.4–2.1-fold risks) whereas diabetes and ischemic heart disease were modest risk factors only among men (1.2–1.4-fold risks). Sociodemographic risk factors included male sex, unmarried status or non-employment; and low education or income among men. Conclusions: All psychiatric disorders, COPD, cancer, spine disorders, asthma, stroke, diabetes, ischemic heart disease and specific sociodemographic factors were independent risk factors for suicide during 8 years of follow-up. Effective prevention of suicide requires a multifaceted approach in both psychiatric and primary care settings, targeting mental disorders (especially depression), specific somatic disorders and indicators of social support.